(untitled) (Bangladesh Journal of Medicine, 2013)
Crohns disease has been considered to be uncommon in Asia Pacific region The study was undertaken to know the extraintestinal manifestations of Crohns disease in Bangladesh and to compare the result with that of other Asian and Western countries. This was an observational study consisting of patients seen in the department of gastroenterology, Bangabandhu Sheikh Mujib Medical University for 20 years (between 1991 and 2010). Individual case records were carefully reviewed with regard to gender, sex and extraintestinal manifestations. A total of 41 patients with Crohns disease were identified. 70.7% were male and 29.3% were female with male to female ratio was 2.4:1. Mean age was 34±11.8 years and peak age group was 21-30 years. The chief extraintestinal manifestations were arthritis, aphthous ulcer in the oral cavity, erythema nodosum and episcleritis. Arthritis was the most frequent among the extraintestinal manifestations. So, Crohns disease should be considered as an important differential diagnosis when a patient presents with bowel symptoms associated with extraintestinal manifestation and thus early recognition and treatment could be possible. DOI: http://dx.doi.org/10.3329/bjmed.v21i2.13611 Bangladesh J Medicine 2010; 21: 58-59